The Diction and Language Style in Sutardji Calzoum Bachri’s Contemporary Poetry (A Study on Stilistics) - Satinem Satinem; Juwati Juwati (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The purpose of this study was to examine contemporary poetry by Sutardji Calzoum Bachri using the stylistic approach. The research method used is based on content analysis. The object of this research is contemporary poems entitled Husspuss, O, Mantera, Sepisaupi, and Tapi. The method used in this study is a qualitative method. The results and discussion in this study in the poems of Husspuss, O, Mantera, Sepisaupi, and Tapi shows that there are many elements of rhyme, rhythm, sound play, and sound repetition that are incorporated in the characteristics of sound and meaning of poetry while the style of language contained in these contemporary poems received less attention from the poet. The poet uses only a few styles of language such as hyperbole and repetition.